2009
DOI: 10.1097/aud.0b013e31819c3e84
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Degradation of Auditory Acuity in Subjects with Normal Hearing Leads to Unequal Precedence Effects

Abstract: These results indicate that a uniform unilateral degradation in auditory acuity leads to increased variability in performance on tasks measuring fusion in the precedence effect. The outcome suggests that variable perception of the precedence effect by individuals with clinically diagnosed hearing loss might be due to factors other than a reduction in auditory acuity per se.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…7 of Saberi and Hafter, 1997). Several studies in addition have shown either an absence or significant reduction of onset dominance for some cue types (e.g., ILDs, Stecker and Brown, 2010), or for individual subjects (Champoux et al, 2009), in infants (Clifton et al, 1981), after extensive experience (Saberi and Perrott, 1990, Saberi and Antonio, 2003), or from top-down influences (e.g., the Clifton effect; Clifton, 1987; Grantham, 1996; Clifton et al, 2002; Keen and Freyman, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…7 of Saberi and Hafter, 1997). Several studies in addition have shown either an absence or significant reduction of onset dominance for some cue types (e.g., ILDs, Stecker and Brown, 2010), or for individual subjects (Champoux et al, 2009), in infants (Clifton et al, 1981), after extensive experience (Saberi and Perrott, 1990, Saberi and Antonio, 2003), or from top-down influences (e.g., the Clifton effect; Clifton, 1987; Grantham, 1996; Clifton et al, 2002; Keen and Freyman, 2009). …”
Section: Discussionmentioning
confidence: 99%